Flow of Electric Currents in Ohmic Contacts of Friction Couples of Braking Devices - Volchenko, D.A.; Javadov, M.Y.; Skrypnyk, V.S.; Volchenko, N.A.; Zhuravlev, D.Yu. (Herald of Azerbaijan Engineering Academy, 2022)
The paper exams the energy levels of contacts in the frictional interaction of metal-polymer and semiconductor materials; ohmic contact in the system: "metal-polymer" and "metal-semiconductor"; the analysis of results. In this case, the height of the potential barrier between their materials in the nearcontact zone and in the "metal-semiconductor" interface with "n" and "p" types of conductivity was taken into account. The different degree of regulation of their surfaces that contribute to the concentration of charge carriers and dislocations of imperfections in the crystal lattice of materials. In this case, thermionic, field and thermal field emissions were formed, accompanied by emerging metal shunts. As for the Fermi energy level, it affects the surfaces in the middle and in the depth of the band gap, near the edge of the valence band, as well as the resulting shift at the edge of the conduction band. All of these factors were under the influence of impulse specific loads and energy load, which contributed to the generation of electric currents of various magnitudes and directions along with alternating thermal currents.